Education and Other Factors Influencing Women Migrants’ Employability and Entrepreneurship - Yolanda Pérez-Varela; Rocío Cárdenas-Rodríguez (Social Sciences, 2024)
Education is considered to be one of the most critical factors when it comes to finding work or starting a business. However, for women migrants, other factors can have an even more decisive influence, since they are starting out with the double disadvantage they face as women and migrants. This manuscript sets out to identify and analyse the individual and external factors that affect the employability and entrepreneurship of women migrants. To do this, we conducted a systematised qualitative review of recent literature. The studies analysed address different aspects of integration and employment but agree on many of the factors that hinder employability and entrepreneurship, such as traditional gender mandates, racism, socioeconomic status, the migration process, age or human capital. However, the scientific literature continues to mask the reality of women migrants who face discrimination or inequalities derived, for example, from their belonging to the LGBTQ+ collective or their functional diversity.